Institutional Achievements Report 2024 - Universidad Peruana de Ciencias Aplicadas (2024)
Created in 1993 in Lima, Perú, Universidad Peruana de Ciencias Aplicadas (UPC) is an innovative, private, research focused, comprehensive educational institution providing undergraduate and graduate degrees notable for academic quality. It seeks to align academic goals with labor market demands and off er students a rigorous, meaningful, and integrated educational experience while promoting research as well as cultural, intellectual, and artistic knowledge.